2017
DOI: 10.1186/s40608-017-0145-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene coding variation and resting metabolic rate in a multi-ethnic sample of children and adults

Abstract: BackgroundResting metabolic rates (RMR) vary across individuals. Understanding the determinants of RMR could provide biological insight into obesity and its metabolic consequences such as type 2 diabetes and cardiovascular diseases.MethodsThe present study measured RMR using reference standard indirect calorimetry and evaluated genetic variations from an exome array in a sample of children and adults (N = 262) predominantly of African and European ancestry with a wide range of ages (10 – 67 years old) and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
1
6
0
1
Order By: Relevance
“…In our study, the novel rs7812133 variant was significantly found in linkage to and LD/association with T2D ( p = 0.04), and, as reported in the previous study [ 25 ], does not contribute to depression. The novel T2D-risk rs8192498 variant detected within our study was previously found to be associated with resting metabolic rate and energy expenditure [ 39 ], but was not found to be associated with suicide in traumatized children [ 40 ] or panic disorder [ 41 ], consistent with our negative finding in depression. The SNP rs77113016 identified to be a novel T2D-risk variant in our familial dataset was previously found in a severely obese child with hyperphagia, but it did not segregate with obesity in other family members [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the novel rs7812133 variant was significantly found in linkage to and LD/association with T2D ( p = 0.04), and, as reported in the previous study [ 25 ], does not contribute to depression. The novel T2D-risk rs8192498 variant detected within our study was previously found to be associated with resting metabolic rate and energy expenditure [ 39 ], but was not found to be associated with suicide in traumatized children [ 40 ] or panic disorder [ 41 ], consistent with our negative finding in depression. The SNP rs77113016 identified to be a novel T2D-risk variant in our familial dataset was previously found in a severely obese child with hyperphagia, but it did not segregate with obesity in other family members [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…The 1q21 region includes the interleukin six receptor, complexes I and II in the electron transport system on mitochondria, and so on. The Hellwege adult study investigated single variant analysis for RMR identified significant loci on chromosomes 15, 1, 17, and 5 in African- and European-American children and adults [ 33 ]. They found the most significant locus was SH3D21 ( p -value 2.01 × 10 −4 ), and they found nominal evidence for association of BMI-associated loci with RMR with rs35433754 (TNKS) within the reported genes for all obesity-related loci from the GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…SH3D21 is expressed in all human tissues and its protein is localized in the nucleus and plasma membrane of the cells 19 . It is not a well-studied gene and in fact an exome array study showing that two SH3D21 SNPs were associated with resting metabolic rates (RMR) 20 is the only available report about SH3D21 function. Employing PICKLES database 21 , we found that SH3D21 gene is essential for the survival of NCIH526 lung cancer cell line, Avana 2018q4 dataset (BF = 9.971, Essentiality Threshold BF = 5).…”
Section: Discussionmentioning
confidence: 99%